Suggestions for the Irish Census of 1881 - Jephson, Henry L. (Statistical and Social Inquiry Society of Ireland, 1880)
The time is rapidly approaching when the next decennial Census for the United Kingdom will be taken. Next April year, one more record of the state of the Kingdom will be added to those already existing: the Acts of Parliament necessary for the purpose must be passed in the course of the present session, and if any additions or alterations are deemed desirable, suggestions should be made without delay, so that they may receive consideration before it is too late.
Read before the Society, 17 February 1880
Keywords: 1881 Census; Demographics; Irish census data; Population; 314.15